ANALISIS DAMPAK KERJASAMA INDONESIA CHILE CEPA TERHADAP NERACA PERDAGANGAN - marsanto adi nurcahyo (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Free trade is a way to increase trade. Indonesia has 15 free trade agreements. Indonesia Chile Comprehensive Economic Partnership Agreement (IC CEPA) is Indonesia's first free trade agreement with Latin American countries. The research question is whether there are differences in the value of imports, exports, and Indonesia's trade balance before and after the enactment of the IC CEPA. This study aims to describe the impact of IC CEPA on trade between the two countries. The data used in this research is quantitative. The type of data is time series data in the form of monthly data from August 2016 to July 2022. The statistical analysis method used in this study is a comparative test. This test compares data before and after the implementation of IC CEPA. Based on the Wilcoxon test, there is a different value of exports and imports before and after IC CEPA entry into force. There is no difference in the trade balance before and after the enactment of the IC CEPA. The impact of IC CEPA has succeeded in increasing the level of trade between Indonesia and Chile. The government should further optimize the market using FTAs ​​by increasing the value of exports